Determining The Best Badminton Starting Service By Using Projectile Motion / Nazhatul Sahima Mohd Yusoff...[et al.] - Mohd Yusoff, Nazhatul Sahima; Alias, Suriana; Rasidi, Nur Fatini; Hisham, Nurfarah Shafiqah; Abdul Wahab, Noor Ain Nazierah (2022)
Badminton is a racquet sport in which players drive a shuttlecock across a net with racquets. There are two forms of starting service in badminton namely the forehand long service and forehand short service. This research will focus on all types of facilities, with the initial height of the service position varying. This research aims to improve shuttlecock starting operation by reducing the amount of time the shuttlecock spends in the air. The projectile motion equation applied is a vector version of Newton's Second Law of Motion, which is aimed at singles players. Using the projectile motion principle, the result will determine the type of starting service that will result in the serviced shuttlecock spending the least amount of time in the air. Since the shuttlecock only spends 1.19983 seconds in the air at a 52° trajectory angle, it can be concluded that forehand short service is the best form of badminton starting service. As a result, it's clear that the higher the starting service spot, the less time the shuttlecock spends in the air. Hence, badminton players should practice forehand short service. In addition, the best trajectory angle made with the sideline is preferable for the best form of badminton starting service.